Economic growth and the diffusion of clean technologies: Explaining Environmental Kuznets Curves - Sjak Smulders; Lucas Bretschger; Hannes Egli (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
Production often causes pollution as a by-product. Once environmental degra- dation becomes too severe, regulation is introduced by which society forces the economy to make a transition to cleaner production processes. We model this transition as a change in "general purpose technology" and investigate how it interferes with economic growth driven by quality-improvements. The model gives an explanation for the inverted U-shaped pollution-income relation found in empirical research for many pollutants (Environmental Kuznets Curve). We provide an analytical foundation for the claim that the rise and decline of pol- lution can be explained by policy-induced technology shifts and intrasectoral changes.
Keywords: O41; Q20; 330; Environmental Kuznets curve; general purpose technology; growth; intrasectoral shifts; Umweltbelastung; Umwelttechnik; Wirtschaftswachstum; Theorie; Environmental Kuznets Curve